2020
DOI: 10.1111/jjns.12372
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for hyperbilirubinemia among newborns from a low‐risk birth setting using delayed cord clamping in Japan

Abstract: AimNeonatal jaundice is a common problem among infants. Among the several risk factors are East Asian race and delayed cord clamping. Birth centers manage low‐risk term deliveries using physiological management, which may include delayed cord clamping. This study aimed to investigate the occurrence of hyperbilirubinemia, a pathological process of jaundice, and its risk factors among neonates born at a Japanese birth center.MethodsThis was a retrospective cohort study. Data were collected from March 2006 to Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although the incidence of jaundice requiring phototherapy in term infants after later cord clamping is slightly increased [14], most studies [22,23] and our study have con rmed that there were no signi cant difference in bilirubin levels and phototherapy rates in neonates of mothers without pregnancy complications between ICC group and LCC group. However, in diabetic pregnant woman, LCC was able to signi cantly increase neonatal bilirubin levels and phototherapy rates compared to ICC.…”
Section: Discussionmentioning
confidence: 42%
“…Although the incidence of jaundice requiring phototherapy in term infants after later cord clamping is slightly increased [14], most studies [22,23] and our study have con rmed that there were no signi cant difference in bilirubin levels and phototherapy rates in neonates of mothers without pregnancy complications between ICC group and LCC group. However, in diabetic pregnant woman, LCC was able to signi cantly increase neonatal bilirubin levels and phototherapy rates compared to ICC.…”
Section: Discussionmentioning
confidence: 42%
“…In Japan, approximately 90% of clinics or hospitals have adopted a policy of ECC, conversely nearly 70% of midwifery birth centers have adopted a policy of DCC [13]. A retrospective cohort survey reported that only 1.8% of neonates required phototherapy at a birth center where DCC was conducted [14]. In addition, a recent observational study reported no significant association between the timing of umbilical cord clamping, infant anemia at 3 to 5 months, and neonatal jaundice [15].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, approximately 90% of clinics or hospitals have adopted a policy of ECC, conversely nearly 70% of midwifery birth centers have adopted the policy of DCC [13]. A retrospective cohort survey reported that only 1.8% of the neonates required phototherapy at a birth center where DCC was conducted [14]. In addition, a recent observational study reported no signi cant association between the timing of umbilical cord clamping, infant anemia at 3 to 5 months, and neonatal jaundice [15].…”
mentioning
confidence: 99%